1986
DOI: 10.1246/bcsj.59.1617
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Plane Vibrations of [1H5]- and [2H5]Pyridines

Abstract: Assignments of the out-of-plane normal vibrations of [1H5]- and [2H5]pyridines were reexamined based on the polarization behavior of the Raman bands and also through the normal coordinate calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The a priori spectrum predicts two fundamentals of about 1300 cm"1: One of them is of large IR intensity (1264 cm"1, B2 species), and the other one (1297 cm"1, A| species) is expected to be weak. With respect to this we have interchanged the IR bands of Stidham and Tucci21 at 1272 and 1319 cm"1 between the symmetry species A| and B2, in accordance with the modifications of Ozono et al 24 The experimental C-D stretching frequencies agree better with the a priori ones than the C-H frequencies, as expected from the lower anharmonicity of the former.…”
Section: Wiberg25supporting
confidence: 80%
See 4 more Smart Citations
“…The a priori spectrum predicts two fundamentals of about 1300 cm"1: One of them is of large IR intensity (1264 cm"1, B2 species), and the other one (1297 cm"1, A| species) is expected to be weak. With respect to this we have interchanged the IR bands of Stidham and Tucci21 at 1272 and 1319 cm"1 between the symmetry species A| and B2, in accordance with the modifications of Ozono et al 24 The experimental C-D stretching frequencies agree better with the a priori ones than the C-H frequencies, as expected from the lower anharmonicity of the former.…”
Section: Wiberg25supporting
confidence: 80%
“…Presently, the a priori SQM force field of pyridazine is considered as the best harmonic force field for pyridazine. With the help of this a priori SQM force field the experimental assignments of Ozono et al 24 have been confirmed basically; however, assignments have been changed in six and four cases for pyridazine-h4 and pyridazine-rf4, respectively. Computed IR intensities are generally in agreement with experiments at a qualitative level.…”
Section: Wiberg25mentioning
confidence: 71%
See 3 more Smart Citations